Avaliação do índice de disfunção temporomandibular em indivíduos com má oclusão de classe III e da sua relação com os aspectos oclusais - Vieira, Ricardo Brandão (2008)
The aim of this study was to evaluate the prevalence of temporomandibular disorders (TMD) in Class III individuals. The sample consisted of 30 individuals witn an average age of 26,4 years, 13 male and 17 female without any orthodontic treatment. The presence of signs and symptoms of TMD were evaluated by an anamnestic questionnaire and clinical examination, including TMJ and muscle palpation, active mandibular range of motion, join noises and occlusal examination. Based on the anamnestic questonnaire, was found a 30% of mild TMD, 3,3% of moderate TMD, 3,3% of severe TMD and 63,3% without TMD. The relationship between DTM and mandibular movements, both articular and muscular palpation, morphologic occlusion and occlusion aspects were analised by student‟s t test for the parametric data and qui-quadrado for de non parametric.It was observed an association between TMD and interferences in non working side. It was concluded that, Class III maloclussion is not associated with the presence of signs and symptoms of TMD.